Transformation of Street Vendors' MSME Income During Religious Events: A Case Study of Sholawatan Al-Busyra in Bangil Field - Sulastri Sulastri (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines the income transformation among micro, small, and medium enterprise (MSME) street vendors during large-scale religious events, with a particular focus on the Sholawatan Al-Busyra gathering in Bangil Square. Using qualitative descriptive methods involving in-depth interviews and direct field observations, the study investigates variations in sales volume, consumer behavior, and profit margins before, during, and after the event. The findings indicate that the vendors' daily income increases substantially by approximately 120–180% during the religious celebration. This economic surge is primarily driven by the influx of visitors, the emergence of emotionally and spiritually motivated purchasing behavior, and the amplification effect of social media promotions. Beyond the direct economic benefits, the event demonstrates how religious activities can serve as a catalyst for local community-based economic development. However, persistent issues such as inadequate infrastructure, limited sanitation facilities, and ineffective waste management pose significant challenges to achieving sustainable economic empowerment for MSMEs.